(untitled) (Journal of Hama University, 2026)
The research aimed to know the degree of contribution of blended education in meeting the requirements of sustainable development among learners of the second cycle of basic education from the point of teachers view in Latakia city, and to know the differences in the estimates of the members of the research sample about the degree of contribution of blended education in meeting the requirements of sustainable development among learners of the second cycle of education Basic according to my variables (number of years of experience, training courses). The descriptive approach was used, and to achieve the objective of the research, a questionnaire was designed consisting of (50) phrases, applied to a sample of (192) teachers and schools from the teachers of the second cycle of basic education in Latakia city. The results of the research showed that the degree of contribution of blended education in meeting the requirements of sustainable development among learners of the second cycle of basic education from the point of teachers view in Latakia city was average, and the results showed that there were no statistically significant differences in the estimates of the members of the research sample on the degree of contribution of blended education in meeting the requirements of sustainable development among learners of the second cycle of basic education in Latakia city according to the variable of the number of years of experience, and the presence of statistically significant differences in their estimates According to the variable of training courses, teachers who have undergone training courses in the field of technology. The research made many proposals, the most important of which are: the adoption of blended learning by educational institutions as one of the modern educational methods, and the inclusion of more concepts of environmentally sustainable development in the curricula at various educational levels.